1998
DOI: 10.1002/pro.5560070611
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic characterization of an intermediate state of human growth hormone

Abstract: The thermal denaturation of recombinant human growth hormone (rhGH) was studied by differential scanning calorimetry and circular dichroism spectroscopy (CD). The thermal unfolding is reversible only below pH 3.5, and under these conditions a single two-state transition was observed between 0 and 100°C. The magnitudes of the A H and ACp of this transition indicate that it corresponds to a partial unfolding of rhGH. This is also supported by CD data, which show that significant secondary structure remains after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
4
8
0
Order By: Relevance
“…2). Similar results were obtained in [14] at acid pH. This is indicative of preservation of a significant part of secondary structure in the denatured protein and supports calorimetric data also pointing to a partial unfolding of hGH during heat denaturation due to aggregation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…2). Similar results were obtained in [14] at acid pH. This is indicative of preservation of a significant part of secondary structure in the denatured protein and supports calorimetric data also pointing to a partial unfolding of hGH during heat denaturation due to aggregation.…”
Section: Resultssupporting
confidence: 88%
“…3, curve 1) is 48 kcal/mol that is more than two times lower than mean values of denaturation enthalpy corresponding to full unfolding of the near-size proteins [9]. A similar result was obtained for hGH in the acid pH interval [14]. The midpoint of the hGH thermal denaturation was equal to 81 ‡C.…”
Section: Secondary Structure and Thermostability Of Hgh And Chimeric supporting
confidence: 65%
“…Thus, the ⌬H v / ⌬H c ratio of > 1.0 suggested that the heat-induced disruption of native structure leads to aggregation of rhGH. These results agree with the previous report that above pH 3.5 the thermal denaturation is irreversible due to the aggregation of rhGH upon unfolding (21). The hydrophilic CyDs increased the unfolding temperature (Tm) of rhGH.…”
Section: Thermal Denaturationsupporting
confidence: 94%
“…37 Aggregation of proteins after lyophilization and reconstitution is often correlated with the extent of loss of native protein structure that occurs during the lyophilization process, with those formulations and conditions that yield the greatest loss of native structure resulting in the most aggregation upon reconstitution. 8 Although numerous studies [38][39][40][41][42][43][44][45][46][47] have demonstrated the role of unfolded or partially unfolded protein molecules in fostering aggregation, the acute loss of structure during lyophilization does not completely explain why aggregation levels increases during storage. In current work, by separating the degradation kinetics between surface and bulk of the solid, we find an alternative explanation for protein aggregation during storage.…”
Section: Kinetic Model For Rhgh Degradation In Lyophilized Samplesmentioning
confidence: 99%